Biological evaluation of polymeric micelles with covalently bound doxorubicin - Větvička, David; Hrubý, Martin; Hovorka, Ondřej; Etrych, Tomáš; Vetrík, Miroslav; Kovář, Lubomír; Kovář, Marek; Říhová, Blanka; Říhová, Blanka (Bioconjugate chemistry, 2009)
The main limitation of contemporary anticancer chemotherapy remains to be the insufficient specificity of the drugs for tumor tissue, which decreases the maximum tolerated dose due to severe side effects. Micellar drug delivery systems based on amphiphilic block copolymers with a very narrow size distribution (10 to 100 nm in diameter) is a novel innovative approach. Here, we report biological and pharmacological properties of polymeric micellar conjugate containing doxorubicin (DOX) covalently bound via hydrolytically cleavable hydrazone bonds to the micelle core. The system had a very low systemic toxicity (almost 20 times lower than free DOX) and long circulation in the bloodstream (with half of the dose after 24 h). Significant accumulation of tested micelles within the tumor was confirmed by fluorescent whole body imaging. Our new micellar system showed promising therapeutic activity against established murine EL-4 T-cell lymphoma; it was found that it is able to completely cure about 75% of tumor-bearing mice (with doses of either 1 x 150 mg DOX kg(-1) or 2 x 75 mg DOX kg(-1), administered i.v.). Moreover, treatment with micelles in cured mice induced tumor-specific resistance. Up to 80% of these mice survived rechallenge with original but not with distinct tumor cells.
Keywords: Lymphoma, T-Cell; Animals; Doxorubicin; Half-Life; hydrolýza; Micelles; Nanoparticles; Polymers; hydrazony; Antineoplastic Agents; Mice; protinádorové látky; poločas; nanočástice; Hydrazones; myši; lymfom T-buněčný; Remission Induction; indukce remise; Hydrolysis; Drug Delivery Systems; doxorubicin; micely; polymery; lékové transportní systémy; zvířata